Improvement of PVDF-co-HFP Hollow Fiber Membranes for Direct Contact Membrane Distillation Applications - Sunarti, Abd Rahman; Rashid, Khalid T.; Alsalhy, Qusay (Informatics Publishing Limited, 2017)
Objectives: Investigation the influence of PVP added into the dope solution with (0, 5, 7 and 9) wt. % on membrane characteristics, structure and performance for DCMD system. Determine the impact of process operating parameters on the performance of the (PVDF-co-HFP) hollow fibre membrane in DCMD applications such as hot feed temperature. Methods/ Statistical analysis Prepared and fabrication a PVDF-co-HFP hollow fibre membrane using a various parentage of PVP (0, 5, 7 and 9 wt. %) as a pore former into the dope solution. Characterisation the structure and morphology of the (PVDF-co- HFP) membrane via FESEM technique. Investigating the performance of the PVDF-co-HFP hollow fiber membrane through a DCMD system. Improvement of PVDF-co-HFP hollow fibers through the adding of PVP molecules into the dope solution was studied. Finding The addition of 5, 7, and 9 wt. % PVP into the dope solution resulted in repressed the sponge-like shapes and promoted the forming of two finger-like shapes. Modified the pore area per unit surface area (porosity) and the pore structure of the synthesized hollow fibres. The pore size of the hollow fibre was enhanced with the addition of 9 wt. % PVP into the dope solution. The PVDF-co-HFP fibres permeate flux with PVP additives was superior to that neat PVDFco- HFP by about 75% at feed temperature (Tf) of 70 °C. The rejected salt factor for all PVDF-co-HFP hollow fibres was over 99.98%. The increase of hot feed temperature led to increased permeation flux for the DCMD process. Application/Improvements: Outcomes give a good indication for the improvement of PVDF-co-HFP hollow fiber via adding the PVP particles onto the dope solution. It can be concluded that the PVDF-co-HFP hollow fiber appropriate for use in DCMD application for seawater desalination.